An Analysis upon the Role of Banking and Non-Banking Financial Companies in Indian Mutual Fund Market: Exploring the Role and Performance of Banking and Non-Banking Financial Companies in the Indian Mutual Fund Market (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The mutual fund industry started in India in a small way with the UTI Act creating what was effectively a small savings division within the RBI. Over a period of 25 years this grew fairly successfully and gave investors a good return, and therefore in 1989. as the next logical step, public sector banks and financial institutions were allowed to float mutual funds and their success emboldened the government to allow the private sector to foray into this area.The most important trend in the mutual fund industry is the aggressive expansion of the foreign owned mu Mai fund companies and the decline of the companies floated by nationalized banks and smaller private sector players. Reliance Mutual Fund. UTI Mutual Fund. ICICI Prudential Mutual Fund. HDFC Mutual Fund and Biiia Sun Life Mutual Fund arc the top five mutual fund company in India.Mutual fund companies in India are influencing the retail investors to invest their surplus funds with or without complete understanding to the mutual funds. It also explores the factors influencing the retail investor to invest in mutual fund schemes. It also seeks to understand the role of SEBI in safeguarding the interest of retail investor in mutual funds. It also identifies the key factor that influences the customer preference for a particular mutual fund. One of the objectives of the present study was to evaluate the financial performance of various mutual fund schemes on different parameters.Performance of mutual fund schemes has been evaluated by using risk to standard deviation, sharp ratio Treynor Index. From the study it was found that, the majority of sample funds have experienced high returns and lower variability on the returns as compared to market portfolios. Earlier, every mutual fund offering resembled the other and this was one reason why the investors were a bit slow in embracing the mutual fund option. Now the time has changed and fund houses have come out with a host of new products that eye investor’s wallet.